Inventando a diferença: ideologias linguísticas e história natural dos discursos do novo biologismo - Vallada, Amanda Diniz (2021)
My goal in this work is to investigate the relations between the mobility of new biologism texts and language ideologies. Since new biologism is the popular and academic discourse that neuroscientifically differenciates women and men, according to Deborah Cameron (2009, 2010, 2014), since textual mobility is the adaptive movements of discourses across different texts and contexts, according to Richard Bauman and Charles Briggs (1990 ), Jan Blommaert (2008) and Michael Silverstein and Greg Urban (1996), since language ideologies are our conceptualizations about language, about linguistic practices and about people engaging in linguistic practices, as indicated by the interpretations of Judith Irvine (1989, 2001), Judith Irvine and Susan Gal (2000) and Paul Kroskrity (2004), and, still, since language ideologies are limiting agents of the possibilities of how a discourse can move, as Mary Bucholtz (2003) observes, I set myself the following question: how is the new biologism recontextualized in Christian events and in science popularizing materials, and how do language ideologies act in such recontextualizations? Ethnographically manufactured with the support of danah boyd and Kate Crawford’s (2012), Christine Hine’s (2000, 2015), Piia Varis’ (2014) and Piia Varis and Mingyi Hou’s (2020) readings of digital ethnography and digital data, my material is formed by Christian events (catholic and protestant) and by texts that aim to popularize neuroscience research on the difference between women and men. With the empirical basis, I discuss the updates of gender relations and sexual difference made up by new biologism. I address the manipulation of repertoires and resources that constitute reentextualized discourse and how language ideologies operate settling traditionally feminine and masculine values and ensuring coherence between discourses, insofar as they connect illustrative metaphorical explanations and varied scientific repertoires. In the end, I conclude that new biologism is a contemporary update of sexual difference, a discourse that is a cultural emblem.